Denotative and Connotative Meaning in Divergent Movie (2014): Roland Barthes Semiotic Analysis: English - Arianti, Dea; Irman Nurhapitudin; R. Myrna Nur Sakinah (Prodi Tadris Bahasa Inggris, 2025)
This research delves into the semiotic analysis of the five factions in the Divergent movie. By examining both the primary and secondary levels of signification, this study values embedded within the visual and narrative symbols of each faction. Through a qualitative descriptive approach, the research analyzes the signifier and signified associated with each faction. The data is then analyzed using Roland Barthes’ semiotic approach; the Primary Significance Levels are as follows: At the primary order of signification, Erudite denotes people who have or show knowledge from academic study. Amity denotes people who are friendly. Candor denotes people who think openly and honestly. Abnegation denotes people who are unselfish. At the primary order of signification, Dauntless denotes people who are brave. The secondary order of significance means that people in the Erudite faction are analytical, know everything, and are logical. People in the Amity faction are nurturing, kind, harmonious, and always happy. People in Candor prioritize truth, honesty, well-structured, and following hierarchy. People in the Abnegation faction are inflexible, selfless, self-sacrificing, and responsible. People in the Dauntless faction are tenacious, protective, and fearless.